Investigation of influence of inulin made from cycoria on structural-mechanical properties of wheat dough - Bondarenko, Yuliia; Bilyk, Olena; Kochubei-Lytvynenko, Oksana; Halykova, Esma; Fain, Albina (My University, 2019)
Bread made from wheat flour in chemical composition is not well balanced for vital ingredients. One of its drawbacks is that with a high content of carbohydrates in it there is little dietary fiber, therefore, it is promising to enrich it with inulin-compliant products. The inclusion of inulin made from chicory in the recipe of wheat bread to influence the formation of the rheological properties of the dough, which will affect the quality of the finished products. Therefore, the object of research in the work is the dough of wheat flour of the first grade, the recipe of which includes inulin made from chicory. During the research, inulin made from chicory «Cosucra» (Belgium) is used in the amount of 5, 10, 15 % by weight of flour. It is established that the addition of inulin leads to an increase in the elastic properties of the dough, especially with an increase in the dose of inulin by more than 10 %. Increasing the dose of inulin up to 15 % and more along with an increase in the elastic characteristics reduces the dough elasticity, causing a significant deterioration in the volume of products. It is proven that a decrease in the specific volume of products and an increase in the elastic characteristics of the crumb are the limiting factors of using inulin products in the formulation of more than 10 % by weight of the flour. Use in the formulation of inulin bread in the amount of 10 and 15 % by weight of flour due to the increase in the elastic properties of the dough leads to a significant deterioration in the volume of products. The taste and aroma of inulin products are inherent in wheat bread. Due to the inclusion of inulin wheat bread in the recipe, the products acquire prebiotic properties, however, the effectiveness of using inulin to improve the quality of finished products is possible with dosing 5 % by weight of flour. For greater enrichment of bakery products with dietary fiber, it is possible to use the dosage of inulin 10 % by weight of flour, but to apply technological measures to improve the quality of products.
Keywords: wheat bread; chicory inulin; elastic properties of dough; dough elasticity; кафедра технології хлібопекарських і кондитерських виробів; кафедра експертизи харчових продуктів; кафедра технології молока і молочних продуктів